STRATEGI PEMASARAN BRAND HOME DECOR MURAKABI CRAFT MENGGUNAKAN DIGITAL MAREKTING PADA PLATFORM INSTAGRAM - Rejune Junita Lesnussa (Jurnal Komunikasi, 2025)
The marketing strategy used by Murakabi Craft includes the use of high- quality visual content, consistent aesthetics, selection of appropriate influencers, active interaction with followers, and use of creative features such as Instagram Stories and IGTV. In addition, they also use digital marketing strategies such as using relevant hashtags, contests, and special promotions to increase brand engagement and awareness. This study aims to reveal the marketing strategy used by the Home Decor Murakabi Craft brand through the use of digital marketing on the Instagram platform. In this fast-paced digital era, social media platforms like Instagram have become an effective means for businesses to promote their products and services to a wider target market. This study uses a qualitative approach by conducting interviews and observing Murakabi Craft and analyzing the content and marketing strategies they use on the Instagram platform